Demand and supply-side barriers and opportunities to enhance access to healthcare for urban poor populations in Kenya: a qualitative study. Issue 5 (6th May 2022) - Bakibinga, Pauline; Kisia, Lyagamula; Atela, Martin; Kibe, Peter M.; Kabaria, Caroline; Kisiangani, Isaac; Kyobutungi, Catherine
Abstract : Objective: To explore the barriers to and options for improving access to quality healthcare for the urban poor in Nairobi, Kenya. Design and participants: This was a qualitative approach. In-depth interviews (n=12), focus group discussions with community members (n=12) and key informant interviews with health providers and policymakers (n=25) were conducted between August 2019 and September 2020. Four feedback and validation workshops were held in December 2019 and April–June 2021. Setting: Korogocho and Viwandani urban slums in Nairobi, Kenya. Results: The socioe-conomic status of individuals and their families, such as poverty and lack of health insurance, interact with community-level factors like poor infrastructure, limited availability of health facilities and insecurity; and health system factors such as limited facility opening hours, health providers' attitudes and skills and limited public health resources to limit healthcare access and perpetuate health inequities. Limited involvement in decision-making processes by service providers and other key stakeholders was identified as a major challenge with significant implications on how limited health system resources are managed. Conclusion: Despite many targeted interventions to improve the health and well-being of the urban poor, slum residents are still unable to obtain quality healthcare because of persistent and new barriers due to the COVID-19 pandemic. In a devolved health system, paying attention to health services managers' abilities to assess and respond to population health needs is vital. The limited use of existing accountability mechanisms requires attention to ensure that the mechanisms enhance, rather than limit, access to health services for the urban slum residents. The uniqueness of poor urban settings also requires in-depth and focused attention to social determinants of health within these contexts. To address individual, community and system-level barriers to quality healthcare in this and related settings and expand access to health services for all, multisectoral strategies tailored to each population group are needed.